2019
DOI: 10.3389/fmicb.2019.02341
|View full text |Cite
|
Sign up to set email alerts
|

Balsacone C, a New Antibiotic Targeting Bacterial Cell Membranes, Inhibits Clinical Isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) Without Inducing Resistance

Abstract: New options are urgently needed for the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections. Balsacone C is a new dihydrochalcone extracted from Populus balsamifera that has been reported previously as being active against Staphylococcus aureus. Here, we evaluate the antibacterial activity of balsacone C against MRSA. Thirty-four (34) MRSA isolates were obtained from hospitalized patients; these isolates were then characterized for their resistance. Most of these MRSA (>85%) were resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…The time‐kill kinetics assay demonstrated that the active antimicrobial compound(s) might have diffused from the bark cloth, but visualization of the fabric using SEM showed biofilms of cells with significant morphological changes in cellular ultrastructure. Bacterial cells became irregular in shape, with invaginations, holes and perforations, which is consistent with bacterial cytoplasmic membrane damage (Côté et al 2019…”
Section: Discussionsupporting
confidence: 62%
“…The time‐kill kinetics assay demonstrated that the active antimicrobial compound(s) might have diffused from the bark cloth, but visualization of the fabric using SEM showed biofilms of cells with significant morphological changes in cellular ultrastructure. Bacterial cells became irregular in shape, with invaginations, holes and perforations, which is consistent with bacterial cytoplasmic membrane damage (Côté et al 2019…”
Section: Discussionsupporting
confidence: 62%
“…2 In addition, some effective antibiotics (clindamycin and vancomycin) can trigger aberrant immunological reaction and other side effects. 3,4 As a consequence, the development of safe, high-efficiency and nonantibiotic antimicrobials against MRSA stains is urgently demanded. As of now, several new therapeutic strategies have proposed, such as photothermal antibacterial (PTA), 5,6 photodynamic antibacterial (PDA) 7,8 or chemodynamic antibacterial (CDA).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers, therefore, examined the extracts obtained from the buds of Populus species for their antimicrobial activity and they isolated from the buds of P. balsamifera the new dihydrochalcone derivatives, known as balsacones [ 16 , 17 ]. The analysis, synthesis, and pharmacological properties of balsacones have been thoroughly studied [ 18 , 19 , 20 ]. In a recent study investigating the biological role of balsacones in treating psoriasis, promising anti-inflammatory and antioxidant effects that may promote clinical recovery in patients with psoriasis were reported.…”
Section: Introductionmentioning
confidence: 99%